Computational Fluid Dynamics Analysis of Elevated Circular Water Tank - Khati, Tanuja; Kaloni, Smita; Narayan, Shashi (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928619);" role="presentation">Water storage tanks play a vital role in <span dir="ltr" style="left: calc(var(–scale-factor)*231.41px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933779);" role="presentation">the society for the supply of water. <span dir="ltr" style="left: calc(var(–scale-factor)*375.07px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917518);" role="presentation">Seismic study of elevated water tank <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951467);" role="presentation">under partially filled condition is a complex problem. The main <span dir="ltr" style="left: calc(var(–scale-factor)*334.63px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.878417);" role="presentation">purpose <span dir="ltr" style="left: calc(var(–scale-factor)*369.43px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.947676);" role="presentation">of the study is to <span dir="ltr" style="left: calc(var(–scale-factor)*441.46px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89759);" role="presentation">perceive <span dir="ltr" style="left: calc(var(–scale-factor)*478.42px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902638);" role="presentation">the seismic <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938316);" role="presentation">behavior of elevated reinforced concrete water tank in earthquake pron<span dir="ltr" style="left: calc(var(–scale-factor)*365.47px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925445);" role="presentation">e areas. For analysis, elevated circular <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.879205);" role="presentation">water tank has been chosen beca<span dir="ltr" style="left: calc(var(–scale-factor)*203.21px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903166);" role="presentation">use, due to high elevation and <span dir="ltr" style="left: calc(var(–scale-factor)*326.11px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899398);" role="presentation">concentration of huge mass, elevated water tanks <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932808);" role="presentation">are more susceptible to horizontal accelerations and become more critic<span dir="ltr" style="left: calc(var(–scale-factor)*368.35px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.957901);" role="presentation">al requiring a rigorous study. <span dir="ltr" style="left: calc(var(–scale-factor)*491.86px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01593);" role="presentation">Va<span dir="ltr" style="left: calc(var(–scale-factor)*503.50px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923111);" role="presentation">rious <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*383.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952472);" role="presentation">hy<span dir="ltr" style="left: calc(var(–scale-factor)*81.86px); top: calc(var(–scale-factor)*383.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.947085);" role="presentation">drodynamic pressures on the wall and <span dir="ltr" style="left: calc(var(–scale-factor)*245.09px); top: calc(var(–scale-factor)*383.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.887384);" role="presentation">base slab <span dir="ltr" style="left: calc(var(–scale-factor)*287.09px); top: calc(var(–scale-factor)*383.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.978539);" role="presentation">of water tank <span dir="ltr" style="left: calc(var(–scale-factor)*347.11px); top: calc(var(–scale-factor)*383.35px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943854);" role="presentation">have been computed by using commercial <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922464);" role="presentation">Computation<span dir="ltr" style="left: calc(var(–scale-factor)*124.10px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933216);" role="presentation">al Fluid Dynamics (CFD) package. <span dir="ltr" style="left: calc(var(–scale-factor)*268.73px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940532);" role="presentation">For partially filled condition, different water heights have been <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*409.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932772);" role="presentation">taken in to consideration for the analysis to study the effect of sloshing on the roof and walls of the water tank. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*423.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942067);" role="presentation">Multiphase and Volume of Fluid (VOF) method were used to analyze the parti<span dir="ltr" style="left: calc(var(–scale-factor)*393.19px); top: calc(var(–scale-factor)*423.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.986607);" role="presentation">ally filled tank. <span dir="ltr" style="left: calc(var(–scale-factor)*458.14px); top: calc(var(–scale-factor)*423.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.8996);" role="presentation">Comparison has <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*436.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.968316);" role="presentation">been made between different tank condition i.e. partially filled condition, full tank condition and empty tank <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*449.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927081);" role="presentation">condition under seismic forces in the workbench platform of ANSYS 18.